Novel and uncommon bryophilous fungi from Brazil - Sheila Miranda Leão-Ferreira; Maria Gabriella Andrade Primo de Souza; Luís Fernando Pascholati Gusmão (Plant and Fungal Systematics)
Bryophilous fungi are an understudied group with unknown biodiversity in tropical regions, and are often underestimated worldwide. In Brazil, research on this ecological group has primarily focused on the southern and southeastern regions. During a survey of bryophilous fungi in the northeastern region, specifically in Bahia State, two novel species, Brachydesmiella bahiensis and Dendryphiosphaera longispora , were discovered. Brachydesmiella bahiensis resembles B. biseptata and B. caudata , but exhibits conidial distal cell morphology between these two species. Dendryphiosphaera longispora has longer conidia than other species within the genus. Also, the uncommon microfungus Dwibeeja sundara was reported for the second time globally. Detailed descriptions and illustrations of each species are provided.